Entrepreneurial dynamics and their impact on economic development in Saudi Arabia - Hanaa Abdelaty Hasan Esmail; Mohammad Jibran Gul Wani; Osama Nashaat Yasin Attia; Heba Elsayed Galal (Future Business Journal)
Abstract Entrepreneurship has emerged as a critical factor in the development of human capital, employment creation, and economic growth in the contemporary era. The critical role of entrepreneurship in promoting innovation and expansion is underscored by the fact that the success of large-scale initiatives frequently depends on innovative ideas. Entrepreneurship is a critical catalyst for the development of human capital and economic expansion due to the synergy that exists between entrepreneurial spirit, market access, and innovative ideas. This study employs the Granger causality analysis of Toda and Yamamoto (J Economet 66:225–250, 1995) to analyze data from 2005 to 2023, with the objective of determining the impact of entrepreneurship on economic development in the Kingdom of Saudi Arabia. The results indicate that entrepreneurship, as evidenced by the rise in the number of entrepreneurs in Saudi Arabia, has a substantial influence on both economic and social dimensions, thereby promoting sustainable development. The increase in entrepreneurial activity is consistent with established economic theories and prior empirical studies, thereby illustrating its function as a catalyst for economic growth and sustainability. The significance of cultivating a supportive environment for entrepreneurship to realize its maximum potential in promoting sustainable and inclusive economic development is emphasized by these findings. The research offers valuable insights for policymakers and stakeholders who are seeking to utilize entrepreneurship as a strategic instrument to achieve national development objectives in Saudi Arabia and beyond.